2024
DOI: 10.2147/ca.s435155
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Usage, Storage, and Expiration Date Checking of Drugs at Dilla University Teaching Hospital

Mesay Milkias Wonte,
Zemedu Aweke,
Hailemariam Getachew
et al.

Abstract: Medications require suitable storage conditions to ensure the potency and efficacy of medicines. Appropriate puttingaway conditions are required to ensure the potency of medications. Medication that is not maintained at the required temperature may further increase the unnecessary burden on the general population's economy due to their lack of potency and efficacy. It is crucial to reduce any wastage, including that of drugs, to increase the efficient use of these scarce resources because there are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the serious health risks associated with medication waste, it is imperative to decrease drug waste and maximise the efficient use of limited resources. 21 In our analysis, a large percentage of narcotic and psychotropic medication cabinets were locked (90.9%). This is greater than a study conducted in Nepal, which found that 71.1% of pharmacies said they stored regulated medications in locked cabinets or lockable drawers.…”
Section: Dovepressmentioning
confidence: 71%
See 1 more Smart Citation
“…Due to the serious health risks associated with medication waste, it is imperative to decrease drug waste and maximise the efficient use of limited resources. 21 In our analysis, a large percentage of narcotic and psychotropic medication cabinets were locked (90.9%). This is greater than a study conducted in Nepal, which found that 71.1% of pharmacies said they stored regulated medications in locked cabinets or lockable drawers.…”
Section: Dovepressmentioning
confidence: 71%
“…5 To enable pharmacies to fulfil their roles in the delivery of healthcare, adequate availability, convenient access, and a sufficient workforce capacity must be guaranteed. 21 Although studies on GDP, GPP, and GSP are numerous, [2][3][4]10,11,13 studies on facilities that significantly affect the practices listed are scarce. Sufficient dispensing and storage facilities are necessary to give the patient plausible services.…”
Section: Introductionmentioning
confidence: 99%